2022
DOI: 10.56093/ijas.v91i12.120808
|View full text |Cite
|
Sign up to set email alerts
|

Study on compatibility of Trichoderma viride with different fungicides

Abstract: Aggressive colonization of T. viride can occurs in diverse environmental condition as a biological control and prevents many soil borne diseases. In this context, laboratory experiment was conducted during 2018-19 at Department of Plant Pathology, Bihar Agricultural University, Sabour, Bhagalpur, Bihar to test the sensitivity of T. viride isolated with selected fungicides to devise the best management practice. In course of investigation, nine fungicides of systemic, non-systemic and their combination were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…Talc, although showing no effects on mycelium growth of C. rosea or T. harzianum, decreased the conidium germination of T. harzianum, probably because this substance can form barriers surrounding conidia, reducing the water and nutrient, and germination of the conidia (IARC, 2010). However, the 80% conidium germination obtained in the presence of talc indicates that it could be used in formulations, since it favored survival and storage of CFUs for up to 150 d at temperatures 0 to 40°C (Bhat et al, 2009;Kumar et al, 2013). Similarly, Rai and Tewari (2016) used talc for moisturizing and liquid formulations containing T. harzianum.…”
Section: Discussionmentioning
confidence: 99%
“…Talc, although showing no effects on mycelium growth of C. rosea or T. harzianum, decreased the conidium germination of T. harzianum, probably because this substance can form barriers surrounding conidia, reducing the water and nutrient, and germination of the conidia (IARC, 2010). However, the 80% conidium germination obtained in the presence of talc indicates that it could be used in formulations, since it favored survival and storage of CFUs for up to 150 d at temperatures 0 to 40°C (Bhat et al, 2009;Kumar et al, 2013). Similarly, Rai and Tewari (2016) used talc for moisturizing and liquid formulations containing T. harzianum.…”
Section: Discussionmentioning
confidence: 99%
“…El grado de acidez o salinidad del suelo es un parámetro importante para el desarrollo de los microorganismos y algunas cepas de hongos tienen requerimientos específicos. Sin embargo, Trichoderma puede adaptarse a diferentes pH ambientales (Kumar, 2013). Existen estudios que demuestran que varias especies de Trichoderma presentan un crecimiento óptimo y una gran tasa de esporulación entre valores de 2-7 de pH (Kumar, 2013).…”
Section: -189 Phunclassified
“…Sin embargo, Trichoderma puede adaptarse a diferentes pH ambientales (Kumar, 2013). Existen estudios que demuestran que varias especies de Trichoderma presentan un crecimiento óptimo y una gran tasa de esporulación entre valores de 2-7 de pH (Kumar, 2013).…”
Section: -189 Phunclassified
“…Kumar et al [11] reported that Carbendazim 12% + Mancozeb 63% has completely inhibited mycelial growth of T.asperellumand had inhibited to cent per cent at 100,200,400 and 800 ppm.…”
Section: Compatibility Of Fungicides With Potential Trichoderma Asper...mentioning
confidence: 99%